Individualism vs socialism - Robertson, Isaac Archie (My University, 1896)
Introduction: To the American people these terms are comparatively new. Twenty years ago they were not used in this country. Today they represent two great economic systems of Government, and just what is implied by each is not yet clearly defined. It will be the object of this paper to put together some of the thoughts of writers of political economy upon these two opposing terms. It will be impossible to go into detail with the many complex subjects arising under each, hence they must, at best, be treated in a very general form. Of the two terms, Socialism is perhaps the older, for it was not till the new form of government began to be contrasted with the old that either of the terms was at all needed. Socialism is especially new and more especially to Americans. Till recently the American considered the socialist as a mysterious being – one type of desperado, who with his foul means and base followers, was planning to strike at the very foundation stones of civilization.
Citation: Robertson, Isaac Archie. Individualism vs socialism. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: American people; Government; Economic systems; Socialism; Individualism; Theses; Manuscripts (documents)